The prevalence of antibiotic resistance genes in Bacteroides fragilis group strains isolated in different European countries. - Eitel, Zsuzsa; Sóki, József; Urbán, Edit; Nagy, Elisabeth (Anaerobe, 2013)
From the 2008-2009 European Bacteroides antibiotic resistance survey, we selected 161 strains for detection of antibiotic resistance genes (cepA, cfxA, cfiA, nim, ermB, ermF, ermG, linA, mefA, msrSA, tetM, tetQ, tetX, tetX1, tet36 and bexA). To facilitate the throughput, the genes were detected by Real-Time PCR. The presence of the genes was correlated with the known MIC data of the strains for the appropriate antibiotics. For the β-lactams, the cepA gene was found in 70.8% of the tested strains (all resistant to ampicillin), but its presence did not correlate with the ampicillin MIC values. The cepA gene occurred at different frequencies among Bacteroides fragilis and non-fragilis Bacteroides strains. The cfxA gene was not a major factor in determining cefoxitin resistance and it was found with higher prevalence in non-fragilis Bacteroides strains than in B. fragilis. Among the five possible clindamycin resistance genes, ermF was the most common and had the highest effect on clindamycin resistance after linA. The ermG-mefA-msrSA combination was found in a set of strains and their linked occurrence implied that they were harbored by the conjugative transposon CTnGERM1. All strains tested were susceptible to metronidazole and none of them harbored nim genes. TetQ was prevalent among both the B. fragilis and non-fragilis Bacteroides strains (78.9 and 84.8%, respectively) and no gene could be clearly linked to tigecycline resistance other than tetQ. BexA, which codes for the fluoroquinolone efflux pump, was found in 7.5% of strains and occurred at different frequencies among B. fragilis and non-fragilis Bacteroides strains, but was represented only in a minor proportion of moxifloxacin-resistant strains.
Keywords: Anti-Bacterial Agents; Bacteroides fragilis; Bacteroides Infections; beta-Lactam Resistance; Drug Resistance, Microbial; Europe; Genes, Bacterial; Humans; Microbial Sensitivity Tests; Prevalence; Real-Time Polymerase Chain Reaction